Phase 1b study of the mammalian target of rapamycin inhibitor sirolimus in combination with nanoparticle albumin–bound paclitaxel in patients with advanced solid tumors. Issue 11 (3rd February 2015) - Abu‐Khalaf, Maysa M.; Baumgart, Megan A.; Gettinger, Scott N.; Doddamane, Indukala; Tuck, David P.; Hou, Shihe; Chen, Nianhang; Sullivan, Catherine; Lezon‐Geyda, Kimberly; Zelterman, Daniel; Hatzis, Christos; Deshpande, Hari; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND The optimal weekly oral dose of sirolimus and intravenous nanoparticle albumin–bound paclitaxel (nab‐paclitaxel) were evaluated. METHODS A phase 1b study was performed to evaluate escalating doses of oral sirolimus (5‐60 mg) on days 2, 9, and 16 with intravenous nab‐paclitaxel (100 mg/m2) on days 1, 8, and 15 in a 28‐day cycle. A run‐in treatment of nab‐paclitaxel (day −14) and sirolimus (day −7) was administered for pharmacokinetic and pharmacodynamic assessments. Clinical trial endpoints included dose‐limiting toxicities (DLTs), maximum tolerated doses, and response rates. Pharmacodynamics included immunohistochemistry for phosphatase and tensin homolog, mammalian target of rapamycin (mTOR), AKT, phosphorylated AKT, S6K1, and phosphorylated S6K1; exploratory gene expression analysis; and [18F]fludeoxyglucose (FDG) positron emission tomography. RESULTS Twenty‐three patients with advanced solid tumors were treated. Fifteen patients had prior taxane therapy. Twenty‐two patients were evaluable for responses. One patient had a complete response, and 5 patients had a partial response (3 confirmed). DLTs were seen in 1 patient each at 10 (grade 3 dyspnea/hypoxia) and 40 mg (grade 4 leukopenia/neutropenia) and in 2 patients at 60 mg (grade 3 fatigue and grade 4 pericardial effusion). Patients with higher expression of posttreatment AKT and a greater decline in FDG activity were more likely to have a treatment response or stable disease. CONCLUSIONS Sirolimus showed an acceptable safety profile at a weekly dose of 40 mg with weekly intravenous nab‐paclitaxel at 100 mg/m2 on days 1, 8, and 15 every 28 days. The posttreatment AKT score and changes in FDG activity may have roles as early predictors of responses to mTOR inhibitors. Cancer 2015;121:1817–1826. © 2015 American Cancer Society.